Hypertension and Experimental Stroke Therapies. Issue 8 (August 2013) - O'Collins, Victoria E; Donnan, Geoffrey A; Macleod, Malcolm R; Howells, David W
Hypertension is an established target for long-term stroke prevention but procedures for management of hypertension in acute stroke are less certain. Here, we analyze basic science data to examine the impact of hypertension on candidate stroke therapies and of anti-hypertensive treatments on stroke outcome. Methods: Data were pooled from 3, 288 acute ischemic stroke experiments (47, 899 animals) testing the effect of therapies on infarct size (published 1978-2010). Data were combined using meta-analysis and meta-regression, partitioned on the basis of hypertension, stroke model, and therapy. Results: Hypertensive animals were used in 10% of experiments testing 502 therapies. Hypertension was associated with lower treatment efficacy, especially in larger infarcts. Overall, anti-hypertensives did not provide greater benefit than other drugs, although benefits were evident in hypertensive animals even when given after stroke onset. Fifty-eight therapies were tested in both normotensive and hypertensive animals: some demonstrated superior efficacy in hypertensive animals (hypothermia) while others worked better in normotensive animals (tissue plasminogen activator, anesthetic agents). Discussion: Hypertension has a significant effect on the efficacy of candidate stroke drugs: standard basic science testing may overestimate the efficacy which could be reasonably expected from certain therapies and for hypertensive patients with large or temporary occlusions.